Herbicide-tolerant sesame (Sesamum indicum L.) genotypes: Identification and prospects for molecular characterization: Herbicide-tolerant sesame (Sesamum indicum L.) genotypes: Identification and prospects for molecular characterization - H H KUMARASWAMY; K T RAMYA; P RATNAKUMAR; R K MATHUR (Journal of Oilseeds Research, 2023)
Weed is a major menace in the early seedling establishment stage and hand-weeding is an uneconomical practice in sesame crop production. Herbicide-tolerance in sesame empowers chemical method of weed control in sesame. In the present study, three genotypes each of the tolerant and susceptible lines, identified under field condition, were screened under controlled condition, using a completely randomized design (CRD), for their differential responses to pendimethalin application at field dosage (750 g/ha). Nucleotide sequences of both target and non-target sites for the herbicide reported in other plant species were used for fetching sesame orthologues and molecular analyses were performed using in silico approaches. Herbicide-tolerant sesame genotypes viz., IC132558, IC131953, and IC1500445, identified in this study help not only understand the underlying molecular mechanism(s) but also serve as germplasm resources useful in breeding herbicide-tolerance in sesame.